2022
DOI: 10.3389/fneur.2022.903273
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep duration with chronic constipation among adult men and women: Findings from the National Health and Nutrition Examination Survey (2005–2010)

Abstract: BackgroundPrevious studies suggested that unhealthy sleep patterns were closely associated with gastrointestinal diseases, but the impact of unhealthy sleep duration on chronic constipation has not been well studied until now. In this study, we aim to explore the association between sleep duration and constipation among males and females.MethodsWe utilized the US National Health and Nutrition Examination Surveys data from 2005 to 2010, and adults (≥20 years old) who completed the sleep and bowel health questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Recent studies have linked sleep disorders with FGID, but most of them were conducted in adults. 76 A meta-analysis done in adults with constipation showed that poor sleep quality increased the constipation prevalence, 7 but we found sleep quality was not related with constipation in children. The discrepancy may be caused by the limited number of studies available in children.…”
Section: Discussionmentioning
confidence: 51%
“…Recent studies have linked sleep disorders with FGID, but most of them were conducted in adults. 76 A meta-analysis done in adults with constipation showed that poor sleep quality increased the constipation prevalence, 7 but we found sleep quality was not related with constipation in children. The discrepancy may be caused by the limited number of studies available in children.…”
Section: Discussionmentioning
confidence: 51%
“…as well as factors like depression scores [14] , sleep duration [15] , and exercise levels [16] .In our sociodemographic assessment, we considered age (treated as a categorical variable), gender, race/ethnicity (spanning categories from Mexican-American to non-Hispanic black), educational attainment, and PIR (with two distinct ranges).…”
Section: Methodsmentioning
confidence: 99%